Pengaruh Temperatur Udara Dingin Terhadap Konsumsi Bahan Bakar pada Gasoline Engine - Basmal; Sugiyarta (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Pratama Mulia Surakarta, 2020)
Gasoline engines are still being developed by motor vehicle manufacturers, both for small vehicles, namely motorbikes and medium-sized vehicles, namely cars with cylinder volumes below 2000 cc. The development of the gasoline engine continues, especially in the fuel system. Regarding the fuel system for production in 2020, it almost uses an injection system that has experienced improvements from the previous generation. The use of this system cannot be separated from the performance of the Electronic Control Unit (ECU) for optimizing the gasoline engine. The change in temperature of the air entering the combustion chamber which tends to be cold will certainly affect fuel consumption. The purpose of this study was to determine the effect of cold air on fuel consumption. The research was conducted at the Automotive Machinery Laboratory of the Pratama Mulia Surakarta Polytechnic in 2020. From an average of 5 experiments using pertalite type fuel in the Toyota Rush engine, the following results were obtained: intake air temperature was 20-250C, at engine speed 1000 rpm = 56 ml, 1500 rpm = 76 ml, 2000 rpm = 90 ml, air temperature 30-320C at engine speed 1000 rpm = 46 ml rpm, 1500 rpm = 63 ml, 2000 rpm = 80 ml. The intake air temperature tends to be low, so the fuel consumption will be less.